Seismic performance of eccentrically braced frames designed by the conventional and equivalent energy procedures. Issue 139 (December 2020) - Yang, T.Y.; Neitsch, J.; Qissab Al-Janabi, Musab Aied; Tung, D.P.
Abstract: Eccentrically braced frame (EBF) is a robust structural system designed for seismic application. The design philosophy for EBF is to utilize the link beams to dissipate the earthquake energy. While such system has been proven to provide sufficient stiffness and strength to prevent the structure from collapse, the structural performance in terms of damage and resilience after strong earthquakes is not explicitly considered. In this paper, a novel design method, named the Equivalent Energy Design Procedure (EEDP), is adopted to design the EBF. EEDP is an alternative design procedure for fused structural systems, where engineers can design the structure to achieve the intended performance objectives at different earthquake hazard levels. To evaluate the performance of the EBF, a 5 storey EBF located in Vancouver, British Columbia, Canada is designed using both the EEDP and the Equivalent Static Force Procedure (ESFP) outlined in the 2015 National Building Code of Canada. Detailed nonlinear dynamic analyses were conducted. The results show that the EEDP designed EBF has better performance with lower initial and repair costs at different levels of earthquake shaking intensities. Highlights: A novel performance-based design procedure (EEDP) is adopted to design eccentrically braced frames (EBFs). Seismic performance assessment of EBFs designed by EEDP and the design method outlined in the National Building Code of Canada (NBCC) is performed. EBFs designed by EEDP have better performance with respect to resilience and initial repair cost at different earthquake shaking intensities.